Aggressive combined pharmacotherapy for heart failure reduces new onset atrial fibrillation. (3rd October 2022) - Tokutome, M; Matsukawa, R; Noma, A; Kisanuki, H; Nakashima, H; Watanabe, T; Sakemi, T; Okabe, K; Okahara, A; Kawai, S; Matsuura, H; Masuda, S; et al.
Abstract: Backgrounds: Heart failure (HF) is a risk factor for new onset atrial fibrillation (AF), and the new onset AF is associated with a worse prognosis in HF patients. It has been reported that renin-angiotensin system inhibitor (RASi), β-blocker and mineral-corticoid receptor antagonist (MRA) prevent the new onset AF in HF patients. However, the effect of combined pharmacotherapy including angiotensin receptor neprilysin inhibitor (ARNI) and sodium glucose co-transporter 2 inhibitor (SGLT2i) on AF is unknown. We investigated the impact of contemporary regimen of combined pharmacotherapy for HF (RASi/ARNI+β-blocker+MRA+SGLT2i) on new onset AF. Methods and results: We retrospectively studied rEF and mrEF patients without AF admitted to our hospital due to decompensated HF between 2015 and 2021 (n=366). Long-term (The mean follow-up was 635±421 days) incidence of new onset AF was investigated with regard to medical therapies. Patients were divided into 2 groups; patients with ≤2 HF drugs (n=181) and patients with ≥3 HF drugs (n=185). Patients with ≤2 HF drugs group were older (77.3 vs 67.0 years old, P<0.001), had a poorer renal function (Cre: 1.66 vs 1.09 mg/dl, P<0.001), and had a higher rate of ischemic heart disease (52 vs 38%, P=0.009), whereas left ventricular systolic function was better (EF: 31.9 vs 27.3%, P<0.001). There were 19 (10.5%) new onsets AF in the ≤2 HF drugs group, whereas only 7 (3.8%) had new onsets AF in the ≥3 HF drugs group (HR 0.36, 95% CI 0.15–0.85, P=0.01). All-cause death and hospitalization for HF were fewer in the ≥3 HF drugs group. A multivariate analysis revealed that ≥3 HF drugs use was an independent negative predictor of new onset AF (HR 0.37, 95% CI 0.15–0.93, P=0.03). Even after a propensity score matching of the clinical variables, the incidence of new onset AF was consistently fewer in the ≥3 HF drugs group (HR 0.36, 95% CI 0.13–0.99, P=0.04). Finally, patients with new onset AF had a higher rate of hospitalization for HF in the studied population (HR 9.68, 95% CI 5.67–16.5, P<0.01). Conclusion: Aggressive combined pharmacotherapy for HF may be associated with fewer new onset AF in patients with HF. Funding Acknowledgement: Type of funding sources: None.